Climate change impacts on a sedimentary coast—a regional synthesis from genes to ecosystems - Christian Buschbaum; L. N. S. Shama; F. L. L. Amorim; S. Brand; C. M. A. Broquard; N. Camillini; A. Cornelius; T. Dolch; A. Dummermuth; J. Feldner; M. S. Guignard; J. Habedank; et al. (Marine Biodiversity, 2024)
Climate change effects on coastal ecosystems vary on large spatial scales, but can also be highly site dependent at the regional level. The Wadden Sea in the south-eastern North Sea is warming faster than many other temperate coastal areas, with surface seawater temperature increasing by almost 2 °C over the last 60 years, nearly double the global ocean mean increase. Climate warming is accompanied by rising sea levels, which have increased by approximately 2 mm yr −1 over the last 120 years. For this sedimentary coast, the predicted acceleration of sea-level rise will have profound effects on tidal dynamics and bathymetry in the area. This paper synthesises studies of the effects of ocean warming and sea level rise in the northern Wadden Sea, largely based on research conducted at the Wadden Sea Station Sylt of the Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research. An increasing rate of sea level rise above a critical threshold will lead to coastal erosion and changes in sediment composition, and may cause the transition from a tidal to lagoon-like environment as tidal flats submerge. This involves changes to coastal morphology, and the decline of important habitats such as muddy tidal flats, salt marshes and seagrass meadows, as well as their ecological services (e.g. carbon sequestration). Ocean warming affects plankton dynamics and phenology, as well as benthic community structure by hampering cold-adapted but facilitating warm-adapted species. The latter consist mostly of introduced non-native species originating from warmer coasts, with some epibenthic species acting as ecosystem engineers that create novel habitats on the tidal flats. Warming also changes interactions between species by decoupling existing predator–prey dynamics, as well as forming new interactions in which mass mortalities caused by parasites and pathogens can play an understudied but essential role. However, Wadden Sea organisms can adapt to changing abiotic and biotic parameters via genetic adaptation and phenotypic plasticity, which can also be inherited across generations (transgenerational plasticity), enabling faster plastic responses to future conditions. Important research advances have been made using next-generation molecular tools (-omics), mesocosm experiments simulating future climate scenarios, modelling approaches (ecological network analysis), and internet-based technologies for data collection and archiving. By synthesising these climate change impacts on multiple levels of physical and biological organisation in the northern Wadden Sea, we reveal knowledge gaps that need to be addressed by future investigations and comparative studies in other regions in order to implement management, mitigation and restoration strategies to preserve the uniqueness of this ecosystem of global importance.